2013
DOI: 10.1093/icb/ict062
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the Symposium--Keeping Time During Evolution: Conservation and Innovation of the Circadian Clock

Abstract: Diurnal and seasonal cues play critical and conserved roles in behavior, physiology, and reproduction in diverse animals. The circadian clock is a transcription-translation feedback loop that represents the molecular mechanism underlying many of these periodic processes, frequently through responses to light. Although much of the core regulatory machinery is deeply conserved among diverse animal lineages, there are also many examples of innovation in the way the clock either is constructed at the molecular-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Since the circadian clock is conserved across species (25), we sought to investigate whether these seven largely uncharacterized genes have functional homologs that might play a role in the mammalian clock pacemaker. We found that five of them (Amph, Gclm, CG14688, CG31324, and CG2277) have orthologs in mouse (Mus musculus), baboon (Papio anubis), and human (Homo sapiens) (table S5).…”
Section: Tissue-specific Cycling Genes and Putative Core Circadian Co...mentioning
confidence: 99%
“…Since the circadian clock is conserved across species (25), we sought to investigate whether these seven largely uncharacterized genes have functional homologs that might play a role in the mammalian clock pacemaker. We found that five of them (Amph, Gclm, CG14688, CG31324, and CG2277) have orthologs in mouse (Mus musculus), baboon (Papio anubis), and human (Homo sapiens) (table S5).…”
Section: Tissue-specific Cycling Genes and Putative Core Circadian Co...mentioning
confidence: 99%
“…The circadian pattern is evolutionarily conserved in human and other organisms, setting daily rhythms in behaviors and physiology (89,119). In mammals, neurons in the suprachiasmatic nucleus (SCN) of the hypothalamus undergo synchronized daily oscillations to generate diurnal patterns of rhythmic circuits of action potential firing (41,132).…”
Section: Circadian Clockmentioning
confidence: 99%
“…Hypoxia signaling and the circadian clock are closely related and heavily cross-communicating pathways ( 5 ). Both pathways are evolutionarily ancient, presenting the first molecular mechanisms allowing living organisms to adapt to environmental stimuli on earth (light/dark cycles and the strongly oxidative environment respectively) ( 47 50 ). Interestingly, the core components of these pathways belong to the same family of transcription factors and are regulated in a very similar fashion.…”
Section: Hypoxia and The Circadian Clock–to Sides Of The Same Coin?mentioning
confidence: 99%